Gamificatie in de methode in het NVT-onderwijs: Onderzoek naar het gebruik van het programma HANNA en de applicatie MONDLY bij scholieren Nederlands - Kántor-Faragó, Márta (Acta Neerlandica, 2024)
Our research explores the effects of digital supplementary course materials used among Hungarian students in secondary education learning Dutch. Our aim was to investigate how supplementary electronic, online and digital course material impacts students aged 15-20 learning Dutch at school as well as their motivation, their experience of flow/anti-flow and their level of Dutch. During the intervention we applied HANNA, a course material developed for tablets, and Mondly, a phone application. Our research focused on 2 main research questions and 5 hypotheses, regarding motivation, motivational pattern and the expected changes, while the hypotheses centred on the flow/antiflow experience, the level of language and its changes. Both the research questions and the hypotheses were established in an abductive framework. We employed qualitative research methods due to the number of our samples. Our research incorporated focusgroup and individual interviews as well. The study was supported by the Foreign Research Group On Language Teaching, a joint project between the Hungarian Academy and the University of Debrecen.